SurfSeat / Nur Alyaa Athilah Adnan ... [et al.] - Adnan, Nur Alyaa Athilah; Mohamad Rafi, Putri Nurul Zahirah; Mohd Hanazi, Nur Hanisa; Halim, Atiqah (2024)
SurfSeat is a unique outdoor seating design that captures the fluidity and grace of ocean waves, drawing inspiration from Malaysia's breathtaking coastal scenery. Crafted from timber, the wavy form of SurfSeat mirrors the natural ebb and flow of the sea, offering a serene and visually stunning experience for the seater. Beyond its aesthetic appeal, SurfSeat is multifunctional, featuring integrated elements such as a cozy nook for cats to play around and a dedicated space for securely parking bicycles. This design not only serves as functional furniture but also as an artistic tribute to Malaysia's enchanting oceans, providing a relaxing and immersive connection to nature.